Correlation of the concept of secularization and secularism (Journal of Philosophy Culture and Political Science, 2018)
The article examines the phenomenon of secularism and the process of its secularization and their role in the history of mankind. As we know, the secularization of the process of reducing the role of religion in the minds of people and the life of society; The transition from society, regulated mainly by religious tradition, to the secular model of social devices on the basis of rational norms. The policy of the state, aimed at reducing the influence and role of religion. The most large-scale cultural transformations in the life of Western European society associated with secularization were adopted as a result of the development of the ideas of the thinkers of the Enlightenment. The term secularization began to reflect the processes of rationalization, the liberation of public consciousness from church influence, the formation of models of an ideal, secular society, the autonomization of art, science, politics, etc. This was embodied in the separation of the church from the state, the school from the church.The analysis presented in the article shows that a secular state that is regulated on the basis of civil, rather than religious norms; Decisions of state bodies can not have a religious justification. You can also say; Secularism is determined not by the presence of contradictions with religious attitudes, but by freedom from such. Declaring a religious holiday on a day off is entirely acceptable in a secular state with thegoal of creating comfortable conditions for the believing part of the population. In a secular state, everyperson has the right to expect that he can live without resorting to religious institutions. In the exampleof our country we see that in a secular state the followers of all faiths are equal before the law.Key words: Secularization, secularism, religion, state, sacral.